Villanueva Morte, C. (2020). Diplomacia y desarrollo del Estado en la Corona de Aragón (siglos XIV-XV). Gijón: Ediciones Trea. 397 pp. ISBN: 978-84-18105-14-2 - María José Cañizares Gómez (Anales de la Universidad de Alicante. Historia Medieval, 2023)
Reseña: Villanueva Morte, C. (2020). Diplomacia y desarrollo del Estado en la Corona de Aragón (siglos XIV-XV). Gijón: Ediciones Trea. 397 pp. ISBN: 978-84-18105-14-2